The Ecological Condition of Mangrove in Bali Beach, Mesjid Lama Village, Talawi Sub District, Batu Bara District, North Sumatera Province. - Ofi Sabrina Sitompul; Yunasfi Djayus; Ahmad Muhtadi Rangkuti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Mangrove is the living plant community between the sea and the land that was influenced by the tides. Bali beach in Mesjid Lama village, Batu Bara Regency of North Sumatera Province has an area of mangrove forest about 637,22 ha. Bali beach still has a natural mangrove ecosystem. But, the coastal has long been used by the local community as a source of livelihood especially mangrove forest logging. This research was aimed to know the ecological condition of mangrove forest and condition of the mangrove waters. This research is done in March 2014 to Mei 2014. This research is done with a purposive sampling method by taking and observing of biotic components which was mangrove vegetation and the measurement of water quality parameters. There are 10 kinds of mangrove which found in the research location, namely Aegiceras corniculatum, Avicennia lanata, A. marina, A. officinalis, Bruguiera cylindrica, B. sexangula, Ceriops tagal, Excoecaria agallocha, Rhizophora mucronata and R. stylosa. Kinds of mangrove substrate at this research is clay, loam and silty loam. The biggest diversity index is in the station II.Keywords : mangrove, the ecological condition, water quality, Batu Bara District.